One-year clinical outcome and predictors of ischemic and hemorrhagic events after percutaneous coronary intervention in elderly and very elderly patients. Issue 8 (12th February 2021) - Monello, Alberto; Chiarito, Mauro; Pivato, Carlo Andrea; Scotti, Andrea; Melillo, Francesco; Munafò, Andrea; Montorfano, Matteo; Margonato, Alberto; Colombo, Antonio; Godino, Cosmo
Abstract : Background: Elderly constitute a high-risk subset of patients but are under-represented in clinical revascularization trials. Our aim was to investigate clinical outcomes and prognosis predictors after percutaneous coronary intervention (PCI) in this population. Methods: Unrestricted consecutive patients with ≥75 years who underwent PCI from 2012 to 2015 were enrolled. The primary ischemic endpoint was the composite of 1-year myocardial infarction, definite/probable stent thrombosis and target vessel revascularization. The primary bleeding endpoint was defined according to the Bleeding Academic Research Consortium (BARC) classification as BARC ≥ 2. Results: We enrolled 708 patients (mean age 80 ± 4): 14% were very elderly patients (≥85 years), 27% of patients were diabetic, 23% had chronic kidney disease (CKD), 17% atrial fibrillation and 37% presented acute coronary syndrome. The primary ischemic endpoint was reported in 67 patients (12%): 29 had myocardial infarction (5%), 25 had definite/probable stent thrombosis (4.4%) and 44 had target vessel revascularization (8%). BARC ≥ 2 bleeding was reported in 43 patients (8%). No differences were found in terms of both ischemic and bleeding events between patients with <85 and ≥85 years. Three-vessel disease and use of bare metal stent were independent predictors of the primary ischemic endpoint. Triple antithrombotic therapy and CKD were the only independent predictors of BARC ≥ 2 bleedings. Conclusions: In our experience, elderly patients reported reassuring efficacy and safety outcomes after PCI, even if ischemic and bleeding events were frequent. Three-vessel disease and the use of bare metal stent were the only predictors of primary ischemic endpoint. Triple antithrombotic therapy and CKD were the only predictors of BARC ≥ 2 bleedings.